2013
DOI: 10.1371/journal.pone.0063731
|View full text |Cite
|
Sign up to set email alerts
|

Huaier Aqueous Extract Inhibits Ovarian Cancer Cell Motility via the AKT/GSK3β/β-Catenin Pathway

Abstract: Traditional Chinese medicine has gained popularity due to its ability to kill tumor cells. Recently, the apoptotic and anti-angiogenic effects of Trametes robiniophila murr (Huaier) have been investigated. The aim of this study was to investigate its effect on cell mobility and tumor growth in ovarian cancer. Cell viability and motility were measured using SRB, scratch and migration assays. Cell apoptosis was analysed by annexin V/PI staining. Using a reverse-phase protein array (RPPA) assay, we analyzed the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 26 publications
6
77
0
Order By: Relevance
“…To detect whether Huaier inhibits proliferation though the pAKT/mTOR/S6 pathway, the protein levels of pAKT, AKT, pS6 (S235-236) and pS6 (S240-244) were evaluated by western blot analysis. The results showed that phosphorylation of S6 at S235-236 and S240-244 was significantly downregulated in three ovarian epithelial cancer cell lines (SKOV3, SKOV3.ip1 and HEY) after 72 h of Huaier treatment, in accordance with the decreased pAKT expression in SKOV3 and SKOV3.ip1 cells, indicating that the pAKT/ mTOR/S6 kinase pathway is involved in the anti-proliferative effects of Huaier (17).…”
Section: Anti-proliferative Effect Of Huaiermentioning
confidence: 78%
See 4 more Smart Citations
“…To detect whether Huaier inhibits proliferation though the pAKT/mTOR/S6 pathway, the protein levels of pAKT, AKT, pS6 (S235-236) and pS6 (S240-244) were evaluated by western blot analysis. The results showed that phosphorylation of S6 at S235-236 and S240-244 was significantly downregulated in three ovarian epithelial cancer cell lines (SKOV3, SKOV3.ip1 and HEY) after 72 h of Huaier treatment, in accordance with the decreased pAKT expression in SKOV3 and SKOV3.ip1 cells, indicating that the pAKT/ mTOR/S6 kinase pathway is involved in the anti-proliferative effects of Huaier (17).…”
Section: Anti-proliferative Effect Of Huaiermentioning
confidence: 78%
“…The same trend was also found in Huaier polysaccharide (HP)-treated hepatocarcinoma cells (MHCC97-H) (21), Huaier extract-treated melanoma cells (A875) (20), ovarian epithelial cancer cells (SKOV3, SKOV3. ip1 and HEY) (17) and breast cancer cells (MCF-7 and MDA-MB-231) (19). The underlying mechanism associated with the proliferation inhibitory effect of Huaier was further revealed in which several well-studied proteins and classic pathways were involved (Fig.…”
Section: Anti-proliferative Effect Of Huaiermentioning
confidence: 96%
See 3 more Smart Citations